Are we there yet? An update on transitional care in rheumatology - McDonagh, Janet E. (Arthritis Res Ther, 2018)
Significant progress has been made in the understanding of transitional care in rheumatology over the last few decades, yet universal implementation has not been realised and unmet needs continue to be reported. Possible explanations for this include lack of evidence as to which model is most effective; lack of attention to the multiple dimensions, stakeholders and systems involved in health transitions; and lack of consideration of the developmental appropriateness of transition interventions and the services/organisations/systems where such interventions are delivered. Successful transition has major implications to both the young people with juvenile-onset rheumatic disease and their families. Future research in this area will need to reflect both the multidimensional (biopsychosocial) and the multisystemic (multiple systems and stakeholders across personal/social/family support networks and health/social care/education systems). Only then will we be able to determine which aspects of transition readiness and service components influence which dimension. It is therefore imperative we continue to research and develop this area, involving both paediatric and adult rheumatology clinicians and researchers, remembering to look beyond both the condition and our discipline. Neither should we forget to tap into the exciting potential associated with digital technology to ensure further advances in transitional care are brought about in and beyond rheumatology.